2011
DOI: 10.3109/02699052.2010.541893
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of misconceptions and expectations of the effects of traumatic brain injury and symptom reporting

Abstract: Based on these preliminary findings, the HIKS may provide a useful measure of the relative tendency to over-generalize or minimize the effects of TBI. However, further research is needed to investigate the reliability and validity of the HIKS prior to clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 29 publications
6
39
3
Order By: Relevance
“…These results are congruent with those of Sadler et al (2012), who showed that people with Alzheimer's disease and developmental disabilities form a cluster that was perceived as high in warmth but low in competence. The finding that participants described the stereotype of people with ABI as low in competence is in accordance with studies of diagnosis threat (e.g., Suhr & Gunstad, 2002), expectations about ABI (e.g., Mittenberg et al, 1992), and misconceptions about and attitudes toward people with ABI (e.g., Linden & Boylan, 2010;Ono et al, 2011). Indeed, in these studies, the cognitive impairments and the resulting loss of Regarding warmth, past studies of attitudes toward people with ABI did not lead us to expect specific ratings.…”
Section: Gen E Ra L Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results are congruent with those of Sadler et al (2012), who showed that people with Alzheimer's disease and developmental disabilities form a cluster that was perceived as high in warmth but low in competence. The finding that participants described the stereotype of people with ABI as low in competence is in accordance with studies of diagnosis threat (e.g., Suhr & Gunstad, 2002), expectations about ABI (e.g., Mittenberg et al, 1992), and misconceptions about and attitudes toward people with ABI (e.g., Linden & Boylan, 2010;Ono et al, 2011). Indeed, in these studies, the cognitive impairments and the resulting loss of Regarding warmth, past studies of attitudes toward people with ABI did not lead us to expect specific ratings.…”
Section: Gen E Ra L Discussionsupporting
confidence: 85%
“…We will examine each of these hypotheses in the following sections by reviewing studies that have examined attitudes toward and misconceptions about people with ABI. Warner, 1988;Guilmette & Paglia, 2004;Hux, Schram, & Goeken, 2006;Ono, Ownsworth, & Walters, 2011). For instance, the misconception that individuals with TBI can forget who they are and not recognize other people but perform perfectly in every other way has been found to be held by 75%-93.4% of participants (Ralph & Derbyshire, 2013).…”
Section: Application Of the Scm To Study Stereotypes Of Mental Disomentioning
confidence: 99%
See 1 more Smart Citation
“…Over 20 years ago, Gouvier and colleagues administered a survey to the lay public and found numerous false beliefs regarding TBIs and TBI survivors (Gouvier et al, 1988). Since that time, several researchers (e.g., Willer et al, 1993;Guilmette and Paglia, 2004;Hux et al, 2006;Chapman and Hudson, 2010;Ono et al, 2011) have confirmed that misperceptions about TBI persist and are widely endorsed across Britain, Australia, the United States and Canada. These misconceptions persist even among those who have personal experience with a brain injury (i.e., having sustained brain injury themselves or having a relative or friend with brain injury) (Chapman and Hudson, 2010).…”
mentioning
confidence: 99%
“…Ono et al [95] Individuals with severe brain injury (n ¼ 13) and individuals without brain injury (n ¼ 99), randomly allocated into brain injury simulation (n ¼ 59) or control (n ¼ 40) groups.…”
mentioning
confidence: 99%